Influence of Externally Elevated Package Temperature on the In-Circuit Performance of Selected Low-Power BJTs and Operational Amplifiers - Ohajianya, Anthony Chibuike; Moses, Odepeli; Ndukwe, Israel Chukwuemeka (Journal of Electronics and Electrical Engineering, 2026)
The electrical characteristics and reliability of semiconductor devices can be significantly affected by increased temperature. This study investigated the effect of temperature on the electrical characteristics of some selected bipolar junction transistors (BC546, BC548, BC549, and C8050) and operational amplifiers (µA741, LF353N, and LM358N) over a temperature range of 25◦C to 200◦C. The parameters investigated include base–emitter voltage, collector–emitter voltage, collector current, and current gain for the transistors, and closed-loop voltage gain for the operational amplifiers. The results show that the base-emitter voltage of the transistors decreased with increasing temperature. The temperature coefficient of the transistors was also found to range approximately from −1.1 mV/◦C to −1.5 mV/◦C. This is in reasonable agreement with theoretical and reported values for silicon BJTs. The variations in the transistors’ collector current and current gain as a result of changes in temperature were found to be device dependent. This reflects the differences in the internal structure and biasing sensitivity of the transistors. For the operational amplifiers, the µA741 showed a noticeable decrease in closed-loop voltage gain at high temperatures, whereas the LF353N exhibited slight variation while the LM358N demonstrated excellent stability within the investigated temperature range. The findings of this research confirm that the performance of even low-power electronic components can be significantly affected by heat generated by other components. It is therefore pertinent for electronic circuit designers and developers to consider the effect of ambient temperature on low-power components, so as to include features to mitigate such adverse effects and ensure the durability of the electronic devices.